1998
DOI: 10.1002/(sici)1098-2736(199810)35:8<845::aid-tea3>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Doing a science project: Gender differences during childhood

Abstract: By adolescence, men's participation and achievement in science exceeds women's. This article reports a case study that examined the beginnings of this gender differentiation during a naturally occurring academic activity that was designed to support and guide young children's interest in doing science. Data were collected during 2 successive years of a science fair for children in Grades 1-6 of a progressive private school. A total of 268 projects were characterized in terms of achievement and area of science.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 20 publications
3
28
0
2
Order By: Relevance
“…In elementary schools, boys preferred the physical sciences, while girls the biological sciences (Adamson, Foster, Roark, & Reed, 1998). Researchers have reported that, in general, girls expressed a greater interest in biology (Dawson, 2000;Prokop, Tuncer, & Chudá, 2007;Uitto, Juuti, Lavonen, & Meisalo, 2006).…”
Section: Role Of Interestsupporting
confidence: 91%
“…In elementary schools, boys preferred the physical sciences, while girls the biological sciences (Adamson, Foster, Roark, & Reed, 1998). Researchers have reported that, in general, girls expressed a greater interest in biology (Dawson, 2000;Prokop, Tuncer, & Chudá, 2007;Uitto, Juuti, Lavonen, & Meisalo, 2006).…”
Section: Role Of Interestsupporting
confidence: 91%
“…For many years, the prevailing theory held that women did not pursue science because they were not as talented at mathematics and science as their male counterparts [5,9,[22][23][24]. A look at the performance of girls in K-12 science today, specifically in recent results of the National Assessment of Educational Progress and the Program for International Student Assessment (PISA), shows that the once-thought achievement gap between girls and boys in mathematics and science no longer exists [5,9,25,26].…”
Section: Literature Review a Gender Equity In Physicsmentioning
confidence: 99%
“…Subjects such as mathematics, chemistry, and physics-physical science in general-are considered masculine, while life sciences are perceived as feminine (Steinkamp & Maehr, 1983). In a striking example of the early divergence of boys' and girls' science interests, Adamson, Foster, Roark, and Reed (1998) found that boys in Grades 1 through 6 tended to choose physical sciences, while girls chose the biological and social sciences, for a science fair project. Out-of-school science experiences for boys and girls may help foster differential preferences, with boys tending to indulge in…”
Section: Volume 8 Issues 3and4mentioning
confidence: 99%
“…Children's at-home experiences when they are very young can affect future learning outcomes in science and math (Farenga, 1995;Harlen, 1992;Kahle, 1990). As elementary school girls and boys form gender-segregated peer groups outside of the classroom, different skills may be developed from group activities that are gender divergent (Adamson et al, 1998). We need to know more about how experiences outside of the classroom may affect girls' and boys' affinity for science and, more specifically, for different types of science.…”
Section: Journal Of Women and Minorities In Science And Engineeringmentioning
confidence: 99%